2012
DOI: 10.1074/jbc.m112.384784
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Prokaryotic Ubiquitin-like Protein-deconjugating Enzyme Is an Unusual Aspartate Amidase

Abstract: Background: Dop is critical for the full virulence of Mycobacterium tuberculosis; however, its mechanism is not understood. Results: Asp-95 was identified as a catalytically significant residue. Conclusion: This work suggests that Asp-95 functions either as a direct nucleophile forming a unique anhydride intermediate or is part of a catalytic center that includes polarized water as the nucleophile. Significance: Understanding the mechanism of Dop can help guide the design and selection of inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In an earlier study it was shown that, during the cycle of catalysis, 18 O-water (H 2 18 O) is incorporated only into Pup and not into Dop (20). Furthermore, the authors showed that hydroxylamine can act as a nucleophile to form Pup-hydroxamate, indicating that during the Dop-catalyzed reaction an activated carbonyl must exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study it was shown that, during the cycle of catalysis, 18 O-water (H 2 18 O) is incorporated only into Pup and not into Dop (20). Furthermore, the authors showed that hydroxylamine can act as a nucleophile to form Pup-hydroxamate, indicating that during the Dop-catalyzed reaction an activated carbonyl must exist.…”
Section: Discussionmentioning
confidence: 99%
“…All Mg 2ϩ ions are coordinated in almost perfect octahedral symmetry. Notably, Asp-94, a residue previously shown to be important for activity (10,13) and proposed to form a mixed anhydride intermediate during catalysis (20), is coordinating Mg 2ϩ at the n1 position.…”
Section: Non-hydrolyzable Atp Analogs Cannot Support Dop Activity-mentioning
confidence: 99%
“…Based on the crystal structure of a PafA D64N dimer solved with the C-terminally fused PupE38-E64 fragment reciprocally provided in trans (4), the C-terminal tail of Pup lines this groove and leads to the putative active site (Figure 1 d , upper panels). Pup E64 is positioned near the triphosphate chain of ATP and surrounded by PafA residues required for pupylation (4, 97), with analogous residues required for Dop activity (11, 97) (Figure 1 d , right panels).…”
Section: Pupylationmentioning
confidence: 99%
“…In another study, Burns et al utilized an electrophilic trap consisting of Pup modified with a C-terminal glutamine mimic to identify a nucleophilic residue in Dop. Labeling of aspartate 95, an atypical nucleophile for a protease, classified Dop as an unusual amidase whereby the deamidation or depupylation reaction proceeds via an anhydride intermediate (61). Although this model is supported by the crystal structure, further experimentation is necessary to definitively prove this unusual protease activity.…”
Section: Depupylationmentioning
confidence: 99%